REL KERETA DAN DINAMIKA TAMBANG TIMAH MASA LALU DI PULAU BANGKA: KAJIAN ARKEOLOGI INDUSTRI - Fahrozi, Muhamad Nofri (Balai Arkeologi Sumatera Selatan, 2018)
Artifacts are the main study in archeological studies, from an artifact, archaeologists try to uncover events that took place in the past. This article seeks to do this process by linking it to other information that has been collected so that a description of past events can be obtained. By focusing on the findings of the Rail in Sungailiat, this article seeks to link past events, especially in the Dutch colonial era. From the results of the research, it is hoped that it can be an inspiration for knowledge in the field of history and technology in the past to be a consideration in making policy in the future.